2018
DOI: 10.1111/1365-2664.13167
|View full text |Cite
|
Sign up to set email alerts
|

Comparing convenience and probability sampling for urban ecology applications

Abstract: Urban forest ecosystems confer multiple ecosystem services. There is therefore a need to quantify ecological characteristics in terms of community structure and composition so that benefits can be better understood in ecosystem service models. Efficient sampling and monitoring methods are crucial in this process. Full tree inventories are scarce due to time and financial constraints, thus a variety of sampling methods exist. Modern vegetation surveys increasingly use a stratified‐random plot‐based sampling to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…Plot-based sampling requires different methods from those of individual-based protocols (sensu Gotelli and Colwell 2001), as plots involve samples of multiple, grouped individuals as replicates, rather than single individuals (Speak et al 2018). Plot-based sampling requires different methods from those of individual-based protocols (sensu Gotelli and Colwell 2001), as plots involve samples of multiple, grouped individuals as replicates, rather than single individuals (Speak et al 2018).…”
Section: Methods For Analyzing Diversity and Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Plot-based sampling requires different methods from those of individual-based protocols (sensu Gotelli and Colwell 2001), as plots involve samples of multiple, grouped individuals as replicates, rather than single individuals (Speak et al 2018). Plot-based sampling requires different methods from those of individual-based protocols (sensu Gotelli and Colwell 2001), as plots involve samples of multiple, grouped individuals as replicates, rather than single individuals (Speak et al 2018).…”
Section: Methods For Analyzing Diversity and Compositionmentioning
confidence: 99%
“…(Further information about the study sites can be found in Table 1 of Blood et al 2016. This field plot measurement and sampling protocol is increasingly being used in cities outside the United States as model input models to estimate urban forest structure and ecosystem services (Yang et al 2017, Speak et al 2018). Other measurements included height, land use, crown width, crown light exposure, and tree location within plot.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations